Strategic Management in Efforts to Increase Regional Original Income (PAD) in the COVID-19 Pandemic - Dewi Ulfa Soebagiya; Rumzi Samin; Fitri Kurnianingsih (Universitas Pendidikan Ganesha, 2023)
The importance of planning contained in the Regional Medium-Term Development Plan (RPJMD) of Kepulauan Riau during the COVID-19 pandemic must carry out a priority program by the Regional Head during his leadership period. This paper aims to examine the development of PAD and indicators of the performance of the RPJMD in Kepulauan Riau. The research method with a qualitative approach by reviewing secondary data in the Accountability Statement Report (LKPJ) of the Regional Head of Kepulauan Riau Province for the 2020 Fiscal Year and other documents, which are then analyzed in-depth using the concept of strategic management as a form of efforts to increase the Regional Original Revenue (PAD) of Kepulauan Riau in the future. The study results show a need to strengthen strategic management of the internal and external environment in the Kepulauan Riau Provincial Government as a form of government readiness in facing economic recovery during the COVID-19 pandemic. Furthermore, the strategic formulation of the Regional Head in realizing his Vision and Mission should focus on the agreed RPJMD so that the achievement of performance indicators creates an increase in Economic Growth, Inflation, Poor Population, and the Gini Index (Gini ratio) can occur during the COVID-19 pandemic in Kepulauan Riau.